ADAPTASI RITUAL DAN PRAKTIK SOSIAL-KEAGAMAAN MAHASISWA DI MASA PANDEMI (STUDI KASUS PADA MAHASISWA FAKULTAS USHULUDDIN DAN FILSAFAT, UIN SUNAN AMPEL SURABAYA) - Wiwik Setiyani Khasbullah (Jurnal Sosiologi Reflektif, 2021)
The COVID-19 pandemic that has been going on for more than two years has changed most socio-religious activities of the community, including many academic communities, especially students. The fact that all educational activities must be carried out online has also changed their religious activities and socio-religious practices. Students use their spare time during the distance learning process with worshipping and doing some social activities at home. This article aims to elaborate on how students adapt to the new situation regarding their religious activities. The research was conducted using a qualitative approach. Data collection techniques used in this research are in-depth interviews with 18 student informants and collecting virtual data through google form. The results showed that students' religious adaptation in worship practices and social activities had helped increase their spirituality and closeness to religion. This conclusion is supported by an increase in the quantity of worship such as the intensity of reading the Qur'an, discipline in conducting obligatory prayers, and the involvement of students in religious-based charity activities in the community.Pandemi Covid-19 di Indonesia selama kurang lebih 2 tahun ini telah mengubah seluruh aktivitas sosial keagamaan masyarakat, tidak terkecuali segment pendidikan khususnya mahasiswa. Fakta bahwa seluruh aktivitas pendidikan harus dilakukan dalam situasi jarak jauh secara langsung juga telah mengubah aktivitas ibadah dan praktik sosial-keagamaan mereka. Mahasiswa mengisi waktu-waktu luang mereka selama pembelajaran jarak jauh dengan aktivitas ibadah dan kegiatan sosial di rumah. Artikel ini bertujuan untuk mengelaborasi bagaimana mahasiswa melakukan adaptasi keagamaan di masa pandemi. Penelitian dilakukan dengan menggunakan pendekatan kualitatif, teknik pengumpulan data melalui wawancara mendalam terhadap 18 informan mahasiswa dan diperkuat dengan data virtual melalui google form. Hasil penelitian menunjukkan bahwa adaptasi keagamaan mahasiswa dalam praktik ibadah dan aktivitas sosial telah membantu meningkatkan spiritualitas dan kedekatan mereka kepada agama. Hal ini dibuktikan dengan peningkatan kuantitas ibadah seperti intensitas membaca Al-Qur’an, kedisiplinan dalam sholat wajib, dan keterlibatan mahasiswa dalam aktivitas charity berbasis keagamaan di masyarakat.